EFFECT OF TRIGONA LAEVICEPS HONEY ON DECREASED GLUCOSE LEVELS IN MALE RATS (RATTUS NOVERGICUS) - Dewi, Sri Ratna (E-Jurnal Medika Udayana; Vol 13 No 4 (2024): E-Jurnal Medika Udayana, 2024)
ABSTRACT   Diabetes mellitus (DM) is a metabolic disease characterized by increased blood sugar levels (hyperglycemia) which occurs due to abnormalities in insulin secretion, insulin action or both. People use many herbal remedies, one of which is Trigona laeviceps honey. This study aims to determine the effect of giving Trigona laeviceps honey on reducing glucose levels in male rats (Rattus novergicus L). This research was an experimental study using 28 Wistar rats (Rattus norvegicus) which were then analyzed by the Kruskall Wallis test to determine differences in glucose levels in the groups. The results showed that there was a decrease in glucose levels in the group given Trigona laeviceps honey and a significant difference in mean glucose levels was obtained based on the treatment group (p 0.000). Keywords : Trigona leaviceps honey, DM, blood glucose.